Будењето на македонскиот национален идентитет во XIX век, преку митот за Филип и Александар Македонски - Dodovska, Ivanka (Фондација Конрад Аденауер, Институт за демократија, солидарност и цивилно општество, 2006)
The nationalism in 19th century was directed in the first place towards the conviction that every nation is special by the fact that it has only one original language, by which can be clearly determined the ethnical expression of being a part of a certain nation. The second very important factor was contained in the insistence of researching the history of the peculiar nation, and also the research for fairy-tales and fables. The leaders of the national revival upon the basis of the historical occasions and the awareness about the question for the identity of the Macedonian nation, indicates two tendencies of fundamental importance, which are gathered around the idea of the historical past of Macedonia, and which are expressing the Macedonian national consciousness for: the antic Macedonian and the new Slavic tradition. The first expressed through the spontaneous verbal tradition through the centuries, for the origin connected with the great Macedonian antic kings, mostly with the myth of Alexander the Macedonian - called the Great, and the second which was representing the historical past of the Slavs, connected and built upon the antic Macedonian folklore and cultural genesis.
Keywords: преродбата, античка историја, Филип Македонски, Александар Македонски